Navigating the Digital Wave of Learning : Indonesian Students’ Perceptions on Emotional during Learning Process - Soesanto, Robert Harry; Dwikristanto, Yanuard Putro; Napitupulu, Bernard Wijaya (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to uncover students’ perceptions of digital learning in terms of emotions. The study is conducted in the context of the post-pandemic era. The research used a cross-sectional design study with a qualitative approach. The research subjects consist of 112 students aged 18-24 years, distributed in several regions of Indonesia. The data were collected by using a Microsoft Forms questionnaire. Data analysis is carried out using a multi-stage process and pattern coding of responses. The findings of this study indicate the presence of themes related to both positive moments and emotional challenges experienced by students during digital learning. Based on these findings, this study suggests that lecturers should continue to practice recognizing students’ contexts so that pedagogical strategies through the application of technology can be implemented to the fullest extent.